2018
DOI: 10.1002/cbin.11069
|View full text |Cite
|
Sign up to set email alerts
|

CFTR inhibits the invasion and growth of esophageal cancer cells by inhibiting the expression of NF‐κB

Abstract: Our study aimed to explore the function of cystic fibrosis transmembrane conductance regulator (CFTR) in esophageal cancer. Twenty patients with esophageal squamous cell carcinoma (ESCC) and 20 patients with esophageal adenocarcinoma (EA) were enrolled in this study. The levels of CFTR and NF‐κB in tumor tissues and adjacent normal tissues were detected, respectively. The expression of CFTR were detected by qRT‐PCR and Western blot in normal esophageal cell line, esophagus squamous cell, carcinoma cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Of note, a previous study reported that downregulation of CFTR was associated with a proportional downregulation of E-cadherin and activation of NFκB/uPA, resulting in disruption of cell polarity, induction of epithelial-to-mesenchymal transition (EMT), and invasion in breast cancer [51]. In addition, CFTR was shown to inhibit invasion by suppressing NFκB in esophageal cancer cells [55]. Increasing evidence also points to direct or indirect regulation of cell-to-cell junctions by CFTR [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a previous study reported that downregulation of CFTR was associated with a proportional downregulation of E-cadherin and activation of NFκB/uPA, resulting in disruption of cell polarity, induction of epithelial-to-mesenchymal transition (EMT), and invasion in breast cancer [51]. In addition, CFTR was shown to inhibit invasion by suppressing NFκB in esophageal cancer cells [55]. Increasing evidence also points to direct or indirect regulation of cell-to-cell junctions by CFTR [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms may also be the cause of CFTR downregulation in cancer, including altered cell signalling or microenvironment changes within tumours. Whatever the cause, CFTR downregulation has been reported in cancer tissues and cells from pancreas [168], prostate [18], breast [18], lung [169,170] and respiratory tract [25], oesophagus [171], colon [24,172] and brain [173]. This downregulation was usually associated with poor prognoses [24,25,169], poor survival rates [172,173] and/or increased malignant behaviours, e.g., metastasis [25,[169][170][171].…”
Section: Is Cftr a Tumour Suppressor Protein?mentioning
confidence: 99%
“…It is also possible that the two mechanisms occur in parallel, rendering CFTR a pleiotropic tumour suppressor. CFTR was also found to inhibit the growth and migration of oesophageal cancer cells by downregulating NF-kB expression [171].…”
Section: Is Cftr a Tumour Suppressor Protein?mentioning
confidence: 99%
“…Also, further analysis suggested it could be employed as an independent predictor for the prognosis of cancer patients [40]. Cystic fibrosis transmembrane conductance regulator (CFTR), a gene mainly expressed in epithelial cells, was found to play pivotal roles in both physiological processes and pathological stages [41]. Specifically, it was illustrated to mediate the innate immune process, which presents more and more impact on cancer regulation due to the emergence of immunotherapy [42].…”
Section: Discussionmentioning
confidence: 99%